2022
DOI: 10.1111/jfb.15193
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying teleost discards in the shark fisheries of Western Australia

Abstract: Quantifying discards is essential for assessing the impact of fisheries on non-target species and the ecosystems in which these fisheries operate. In Western Australia (WA), fishers are required only to report catches of retained species. For the currently operating shark fisheries of WA, the authors quantified catch time series of discarded teleosts using data from at-sea observers collected since 1993. Sixty-two teleost species were observed in the catch of which 20 were routinely discarded. The most commonl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Although not retained, K. sydneyanus and Kyphosus cornelii, referred to collectively as K. cornelii, historically constituted the largest component, by weight, of the scalefish catch in the Temperate Demersal and Gillnet and Demersal Long-line Fishery (TDGDLF) off south-western Australia (McAuley and Simpfendorfer 2003). More recently, total annual catch from the TDGDLF has declined due to management decisions and the consequent declining effort (Watt et al 2021), with K. sydneyanus and K. cornelii now estimated to constitute a negligible proportion of the catch in comparison to retained scalefish and elasmobranchs (Braccini et al 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not retained, K. sydneyanus and Kyphosus cornelii, referred to collectively as K. cornelii, historically constituted the largest component, by weight, of the scalefish catch in the Temperate Demersal and Gillnet and Demersal Long-line Fishery (TDGDLF) off south-western Australia (McAuley and Simpfendorfer 2003). More recently, total annual catch from the TDGDLF has declined due to management decisions and the consequent declining effort (Watt et al 2021), with K. sydneyanus and K. cornelii now estimated to constitute a negligible proportion of the catch in comparison to retained scalefish and elasmobranchs (Braccini et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…While K. sydneyanus is not targeted by commercial or recreational fishers and the numbers of individuals caught as bycatch in the commercial gillnet fishery off southern Western Australia is now considered to be negligible (Braccini et al 2022), they have historically been taken in large quantities in this fishery (McAuley and Simpfendorfer 2003). Attributes such as schooling behaviour and high site fidelity of kyphosids (Ferguson et al 2013;Pillans et al 2017) lend these species, when caught, to be caught in large numbers, as is demonstrated by the very high catches of G. tricuspidata in New South Wales (Gray et al 2010).…”
mentioning
confidence: 99%